Trends of Implementation of Paper Standards towards Paper Preservation: a Librarian's Point of View - Majumdar, Suchismita; Banerjee, Swapna (Journal of Information and Knowledge, 2013)
Preservation of Paper based resources is the concern of the librarians, conservators and archivists through ancient times and is expected to remain so in the times to come. Paper quality hereby plays a vital role. To chalk out the requirements for preservation of a particular paper document, published by a particular publisher, or a paper on which something is written, it is highly intended to be informed about the quality of the paper. Standards for paper quality are being implemented. What is the trend and pace of implementation of standards for paper quality? What is the trend of the paper quality as used by the publishers? Accordingly, what is the trend of the pulp and paper manufacturing industry? This paper tries to search these answers considering data from the year 1980 to 2010, precisely from a librarian’s point of view.